Identification of familial colorectal cancer and hereditary colorectal cancer syndromes through the Dutch population-screening program: results ofa pilot study. (2nd October 2016) - van Erp, Sanne J. H.; Leicher, Laura W.; Hennink, Simone D.; Ghorbanoghli, Zeinab; Breg, Simone A. C.; Morreau, Hans; Nielsen, Maartje; Hardwick, James C. H.; Roukema, Jan A.; Langers, Alexandra M. J.; de Vos tot Nederveen Cappel, Wouter H.; Vasen, Hans F. A.
Abstract: Objectives: In 2014, a population-screening program using immuno-faecal occult blood testing (I-FOBT) has started in the Netherlands. The aims of this study were to evaluate the proportion of individuals in the Dutch screening program with a positive I-FOBT that fulfill the criteria for familial colorectal cancer (FCC) and to evaluate the proportion of participants that needs genetic counseling or colonoscopic surveillance. Material and methods: This retrospective observational study was performed in two large hospitals. Individuals aged between 55 and 75 years with a positive I-FOBT that underwent colonoscopy were included. A detailed family history was obtained in all individuals. Results: A total of 657 individuals with a positive I-FOBT test underwent colonoscopy. A total of 120 (18.3%) participants were found to have a positive family history for CRC, 20 (3.0%) fulfilled the FCC criteria, 4 (0.6%) the Bethesda guidelines and 1 (0.2%) participant the Amsterdam criteria. Multiple adenomas (>10) were found in 21 (3.2%) participants. No cases of serrated polyposis were identified. Based on these criteria and guidelines, a total of 35 (5.3%) required referral to the clinical geneticist and the relatives of 20 (3.0%) participants should be referred for surveillance colonoscopy. Conclusion: Obtaining a detailed family history at the time of intake of participants with a positive I-FOBT in the Dutch surveillance program increased the identification of participants with familial CRC.